2017
DOI: 10.1513/annalsats.201608-625oc
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, Sleep Quality, and Quality of Life in Mild to Moderate Parkinson’s Disease

Abstract: Insomnia symptoms, OSA, and subsequent poor sleep quality are prevalent in Parkinson's disease. In this single-center, exploratory study, we found that insomnia and poor sleep quality, but not OSA, play important roles in determining overall quality of life for patients with this disease. Clinical trial registered with www.clinicaltrials.gov (NCT02034357).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Considering non-motor symptoms, sleep is evaluated in 11 studies, predominantly using wearable devices. This patient-relevant [108] 'outcome' in PD is very complicated with various sleep diagnoses being more common in the PD population (e.g., REM sleep behaviour disorder, restless legs syndrome, insomnia) [109]. Other non-motor outcomes remain largely unmeasured in the home environment.…”
Section: What Is Being Measured?mentioning
confidence: 99%
“…Considering non-motor symptoms, sleep is evaluated in 11 studies, predominantly using wearable devices. This patient-relevant [108] 'outcome' in PD is very complicated with various sleep diagnoses being more common in the PD population (e.g., REM sleep behaviour disorder, restless legs syndrome, insomnia) [109]. Other non-motor outcomes remain largely unmeasured in the home environment.…”
Section: What Is Being Measured?mentioning
confidence: 99%
“…Surveys suggest that insomnia affects 46% of PD patients; vivid dreams, 34%; acting out while dreaming, 36%; and restless legs syndrome, 42% . Depression, anxiety, cognitive problems, stress, and daytime sleepiness have been found to result from these conditions, and sleep disorders in PD have a negative impact on patients’ quality of life (QoL) …”
Section: Introductionmentioning
confidence: 99%
“…1 Depression, anxiety, cognitive problems, stress, and daytime sleepiness have been found to result from these conditions, and sleep disorders in PD have a negative impact on patients' quality of life (QoL). 9,10 On the other hand, using the King's Parkinson's Disease Pain Scale (KPPS), 11 the syndromic nature of pain has been formally subdivided into several patterns. Prior research has shown that the prevalence of pain is 68 to 81% in PD patients [12][13][14] and that it can be manifested in several modalities, such as musculoskeletal (41-89%), dystonic (15-17%), radicular-neuropathic (27-32%), and central pain (4-22%).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep dysfunction is prominent across the spectrum of neurodegenerative conditions, occurring in 40 to 0% of patients [1][2][3][4][5]. It is a key determinant of patients' quality of life [6], falls risk [7], and progression to institutionalization [8][9][10][11], as well as caregiver burden and health [12][13][14]. It should therefore be a priority in the clinical care of patients with neurodegenerative disease but is currently typically overlooked.…”
Section: Introductionmentioning
confidence: 99%